2010
DOI: 10.1007/s00424-010-0863-8
|View full text |Cite
|
Sign up to set email alerts
|

A comprehensive analysis of gene expression profiles in distal parts of the mouse renal tubule

Abstract: The distal parts of the renal tubule play a critical role in maintaining homeostasis of extracellular fluids. In this review, we present an in-depth analysis of microarray-based gene expression profiles available for microdissected mouse distal nephron segments, i.e., the distal convoluted tubule (DCT) and the connecting tubule (CNT), and for the cortical portion of the collecting duct (CCD; Zuber et al., Proc Natl Acad Sci USA 106: [16523][16524][16525][16526][16527][16528] 2009). Classification of expressed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
37
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(38 citation statements)
references
References 86 publications
1
37
0
Order By: Relevance
“…Using freehand microdissection, previous studies established transcriptome data for the renal distal convolution, 21,22 but the gradual transition from the DCT to the connecting tubule makes it almost impossible to precisely define the border between these functionally different segments. Moreover, the low yield of microdissection requires amplification of obtained cDNAs, which bears the risk of increased false-positive and false-negative results.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Using freehand microdissection, previous studies established transcriptome data for the renal distal convolution, 21,22 but the gradual transition from the DCT to the connecting tubule makes it almost impossible to precisely define the border between these functionally different segments. Moreover, the low yield of microdissection requires amplification of obtained cDNAs, which bears the risk of increased false-positive and false-negative results.…”
Section: Discussionmentioning
confidence: 99%
“…To test for functional effects, we injected Xenopus oocytes with cRNAs encoding NCC together with PP1a, the catalytic subunit of PP1, or a constitutively active variant of I-1 (T35D). 31 I-1 (T35D) substantially increased 22 Na uptake ( Figure 3B). PP1a slightly reduced 22 Na uptake, but the differences did not reach statistical significance.…”
Section: I-1 Regulates Ncc Phosphorylationmentioning
confidence: 96%
See 2 more Smart Citations
“…However, the GPCRs discussed here may only be the tip of the iceberg. Indeed, by analyzing transcriptomic data, Pradervand et al [214] have identified In our opinion, the next important challenge is not only to discover new regulatory processes but also to understand how they are linked. As shown in this review, the activation of some GPCRs induces the stimulation of Na + reabsorption whereas others trigger the inhibition of Na + transport.…”
Section: Resultsmentioning
confidence: 99%